Contrast Sensitivity Testing in Retinal Vein Occlusion Using a Novel Stimulus - Mishra, Shubhendu (Transl Vis Sci Technol, 2020)
PURPOSE: This study evaluated a novel tool known as the motion diamond stimulus (MDS), which utilizes contrast-generated illusory motion in dynamic test regions to determine contrast sensitivity (CS). METHODS: Patients with treated unilateral retinal vein occlusions (RVOs) underwent three assessments: the MDS, the Pelli-Robson (PR), and the National Eye Institute's Visual Function Questionnaire (VFQ-25). The MDS assessment produced two data end points, α and β. The α value represents the overall contrast threshold level and the β value serves to quantify the adaptability of the visual contrast system. The CS parameters from the MDS and log CS PR output values were used to compare RVO eyes (n = 20) to control eyes (n = 20). RESULTS: The study participants had a mean composite VFQ-25 score of 89.5 ± 10.4 on the VFQ-25. A significant difference was observed between the RVO eyes and the control eyes in PR log CS scores (P value = 0.0001) and in MDS α value (P value = 0.01). No difference in MDS β value was found between the study groups (P value = 0.39). CONCLUSIONS: The results for the MDS assessment's α parameter corroborated the PR scores, suggesting contrast sensitivity threshold impairment in patients with RVO. No significant difference in β value was observed, suggesting that adaptability of the visual system is maintained in treated RVO eyes. TRANSLATIONAL RELEVANCE: Currently, visual complaints cannot be entirely identified by Snellen visual acuity alone. The MDS offers potentially a more complete look at visual function, by including contrast sensitivity and may be able to quantify changes otherwise overlooked in retinal disease progression.